2011
DOI: 10.4314/ajfand.v6i2.71739
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological studies of cockroaches from three localities in Gaborone, Botswana

Abstract: Cockroaches have become the most common pests in a majority of households in Gaborone, the capital city of Botswana Their presence has always raised safety concerns, especially as carriers of food-borne pathogens and food-spoilage organisms. To address the safety issues, bacteriological investigations were carried out on cockroaches trapped from the kitchens and toilets of three localities in Gaborone, households in Botswana. The bacterial, total spore forming, Bacillus cereus, coliforms and E. coli counts fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…The S. flexneri isolate detected from cockroaches body substantiated the previous report made in Ghana [ 26 ], Botswana [ 12 ], Iran [ 30 ], and Ethiopia [ 14 ]. The isolation of S. flexneri from the gut of cockroaches in the FHEs might be a reflection of recent infected source as dose feeding experiments demonstrated that maximum survival shedding duration of cockroaches for Shigella was less than four days after they fed with standard inoculums via contaminated food [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The S. flexneri isolate detected from cockroaches body substantiated the previous report made in Ghana [ 26 ], Botswana [ 12 ], Iran [ 30 ], and Ethiopia [ 14 ]. The isolation of S. flexneri from the gut of cockroaches in the FHEs might be a reflection of recent infected source as dose feeding experiments demonstrated that maximum survival shedding duration of cockroaches for Shigella was less than four days after they fed with standard inoculums via contaminated food [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, a total of 1140 adult cockroaches, 730 from restaurants and 410 from cafeterias, were included for microbiological investigation. Since the cockroach infestation is high and cockroaches may probably carry the same amount of bacteria cockroaches were taken as a pool of 10 cockroaches as one batch [ 8 , 12 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is known that isolates are the main causes of diverse types of nosocomial and community acquired infections, notably pneumonia, urinary tract infection, respiratory tract infection, skin infections, septicemia, and gastroenteritis [ 18 ]. Likewise previous reports have also indicated that the above-mentioned bacteria pathogens were the common isolates from cockroaches [ 10 , 19 21 ].…”
Section: Discussionsupporting
confidence: 67%
“…More than 33.3% of cockroach isolates have shown resistance to antimicrobials (Mpuchane et al, 2006). There are also many different virulence factors, which are usually encoded by plasmids, chromosomes, or bacteriophages (Tham, 2012).…”
Section: Introductionmentioning
confidence: 99%